2001
DOI: 10.1577/1548-8659(2001)130<0018:darffa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Determining a Regional Framework for Assessing Biotic Integrity of Virginia Streams

Abstract: The utility of an index of biotic integrity (IBI) depends on its ability to distinguish anthropogenic effects on biota amid natural biological variability. To enhance this ability, we examined fish assemblage data from least‐disturbed stream sites in Virginia to determine the best way to regionally stratify natural variation in candidate IBI metrics and their scoring criteria. Specifically, we examined metric variation among physiographic regions, U.S. Environmental Protection Agency ecoregions, and drainage b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…1986; Harris & Silveira 1999), quantifying intensity of disturbance (Mebane 2001), and determining natural variation in fish communities (Karr et al. 1986; Schlosser 1990; Smogor & Angermeier 2001). Additionally, these systems are important to assessing restoration efforts (Hughes et al.…”
Section: Introductionmentioning
confidence: 99%
“…1986; Harris & Silveira 1999), quantifying intensity of disturbance (Mebane 2001), and determining natural variation in fish communities (Karr et al. 1986; Schlosser 1990; Smogor & Angermeier 2001). Additionally, these systems are important to assessing restoration efforts (Hughes et al.…”
Section: Introductionmentioning
confidence: 99%
“…This is a standard result because both temperature and flow play critical roles in structuring fish assemblages in rivers (Matthews, 1998;Jackson et al, 2001). The dummy variable being significant confirms that fish assemblages are related to the physiography of the landscape (Resh et al, 1988;Smogor and Angermeier, 2001). As stated above, NSP has its origin in land use, mainly from both agricultural activities and urbanization in a watershed (Wang et al, 1997;Harding et al, 1998;.…”
Section: Discussionmentioning
confidence: 70%
“…A dummy variable was included in order to assess whether regional heterogeneity in the basin had an effect on the models. Resh et al (1988) and Smogor and Angermeier (2001) noted that both natural and human disturbances in rivers have different consequences according to the physiography of the watershed (i.e. mountains, piedmont or floodplain).…”
Section: Stepwise Regression Modelingmentioning
confidence: 99%
“…But in some cases, authors found ambiguous or positive relationships between agricultural land use and IBI scores (Gordon andMajumder 2000, Couch 1997). Because the metrics used in these indices represent a variety of trophic levels, taxonomic groups, functional characteristics, and tolerance ranges, modifications must often be made to reflect regional or local characteristics (Fausch et al 1984, Karr et al 1986, Barbour et al 1999, McCormick et al 2001, Smogor and Angermeier 2001. Such modifications limit the comparability of these studies across landscapes.…”
Section: Introductionmentioning
confidence: 99%